The applicability of eye‐controlled highlighting to the field of visual searching. (26th February 2018) - Wang, Qijun; Sun, Mengdan; Liu, Hongyan; Pan, Yunxian; Wang, Li; Ge, Liezhong
Abstract: Objective: With the increasing amount of information presented on current human–computer interfaces, eye‐controlled highlighting has been proposed, as a new display technique, to optimise users' task performances. However, it is unknown to what extent the eye‐controlled highlighting display facilitates visual search performance. The current study examined the facilitative effect of eye‐controlled highlighting display technique on visual search with two major attributes of visual stimuli: stimulus type and the visual similarity between targets and distractors. Method: In Experiment 1, we used digits and Chinese words as materials to explore the generalisation of the facilitative effect of the eye‐controlled highlighting. In Experiment 2, we used Chinese words to examine the effect of target‐distractor similarity on the facilitation of eye‐controlled highlighting display. Results: The eye‐controlling highlighting display improved visual search performance when words were used as searching target and when the target‐distractor similarity was high. No facilitative effect was found when digits were used as searching target or target‐distractor similarity was low. Conclusions: The effectiveness of the eye‐controlled highlighting on a visual task was influenced by both stimulus type and target‐distractor similarity. These findings provided guidelines for modern interface design with eye‐based displays implemented.